KESANTUNAN BERBAHASA DALAM NOVEL IPAR ADALAH MAUT KARYA ELIZASIFAA - Rahmawati, Febiana; Gunawan, Hafiz; Hakim, Man; Kusmiarti, Reni (Jurnal Membaca Bahasa dan Sastra Indonesia, 2025)
The problem in this study is how the use of politeness maxims according to Leech in the novel Ipar is Maut by Elizasifaa. The purpose of this study is to describe the use of politeness maxims according to Leech in the novel Ipar is Maut by Elizasifaa. The benefits of this study are divided into two, namely theoretical benefits, namely, the results of this study are expected to add to the treasury of politeness studies, in this case politeness in spoken language in novels and practical benefits, namely, for readers, for students, and for further researchers. The data in this study are in the form of speech containing politeness maxims in the novel Ipar is Maut by Elizasifaa. The method used in this study is a descriptive method. Data collection techniques use reading and note-taking techniques. The results of this study are that there are 6 politeness maxims used. The results of the study on the use of the most dominant politeness maxims used in the novel Ipar adalah Maut by Elizasifaa are the politeness of language in the maxim of sympathy, which is 24 utterances, and the least is the maxim of simplicity as many as 2 utterances. From the total collected, there were 79 utterances that used the principle of politeness.